PRAKTIK CURANG PENGGUNAAN TIMBANGAN DALAM JUAL BELI DIPASAR ANGGREK KABUPATEN KUBU RAYA - NIM. A1011151233, YAYANG KURNIA (Fakultas Hukum Universitas Tanjungpura, 2022)
ABSTRACTTrading can occur anywhere, not only in the market but also in places that are considered to be able to buy and sell. The market is also a container in which it is a meeting place or interaction between sellers and buyers with a trading system. Kubu Raya has two types of trade, namely modern markets and traditional markets, the development of a modern shopping center in Kubu Raya in 2017 with the establishment of Transmart and having attractive facilities is an advantage of modern markets compared to traditional markets which do not have attractive facilities such as traditional markets. modern markets, but traditional markets have advantages that modern markets do not have, namely the bargaining system. Unfair competition can trigger business actors to produce goods or services with minimal production costs so that they can generate maximum profits. In buying and selling transactions in traditional markets, scales are used as a benchmark to ensure the accuracy of the goods being traded. The scales can be misused by traders in various ways so that the weight of an item is not as it should be. In buying and selling honesty and truth are the most important values.The word method comes from the Greek word